Sleep quantity and quality and cardiometabolic risk factors in Indigenous Australians. (11th June 2020) - Yiallourou, Stephanie R.; Maguire, Graeme P.; Carrington, Melinda J.
Abstract: Poor sleep is associated with increased risk of cardiovascular disease (CVD). Indigenous Australians have 1.3 times higher risk of CVD compared to non‐indigenous Australians. However, there are limited data describing sleep problems and cardiometabolic risk in this population. This study aimed to investigate sleep quantity and quality in indigenous Australians and assess its association with cardiometabolic risk. Two hundred and forty‐five indigenous Australians aged > 18 years were recruited via convenience sampling from communities in the Northern Territory and Queensland. Sleep quantity and quality was assessed subjectively with questionnaires including the Epworth Sleepiness Scale. In a sub‐population ( n = 46), objective sleep assessment was performed over three nights of actigraphy. Cardiometabolic risk measures included glycated haemoglobin, lipids, anthropometric measurements and sitting blood pressure. Sleep duration measured subjectively and objectively averaged 7.5 ± 2.0 hr/night; however, over one‐third of participants (self‐report 35%; actigraphy 39%) obtained < 7 hr/night. Overall, more than a third of participants experienced poor‐quality sleep, with 27% reporting severe daytime sleepiness (ESS score > 10) and a high number of objectively measured awakenings/night (6 ± 4). Short sleep duration (<6 hr/night) measured both subjectively and objectively was an independent predictor of diastolic ( β = 5.37, p = .038) and systolic blood pressure ( β = 14.30, p = .048). More objectively measured night‐time awakenings were associated with increased glycated haemoglobin levels ( β = 0.07, p = .020) and greater sleep fragmentation was associated with lower high‐density lipoprotein levels ( β = −0.01, p = .025). A large proportion of indigenous Australians experienced short sleep durations and had significant sleep disruption. Poor sleep quantity and quality may contribute to heightened cardiometabolic risk in this population.